Design of Highly Coherence MIR Supercontinuum Generation in W-type Index Chalcogenide Fiber - Mustafa Khamis (High-Brightness Sources and Light-driven Interactions, 2018)
This paper proposes the W-type index chalcogenide fiber to generate fully coherent MIR supercontinuum generation. Our fiber design has high nonlinear coefficient, flattened dispersion profile and a tight confinement of the mode within the core.